Complications of illegal abortion in the suburbs of Tehran: A 9-year cross-sectional study - Roya Rashidpouraie (Wolters Kluwer Medknow Publications, 2021)
Background: Illegal abortion is a common way to terminate unintended pregnancy. It may be associated with severe complications and may raise maternal mortality and morbidity rate. Illegal abortion is one of the important concerns in health system. In our study, we consider illegal abortion claims in Medical Council court in the suburbs of Tehran. Materials and Methods: A retrospective study was conducted. Data were extracted from registered judicial complainant cases of illegal abortion in Shahriyar medical court, Iran, during 2009–2017. Results: There were 751 registered claims during 2009–2017. Among them, a total of 95 gynecological claims were included in the study. Four (4.2%) registered claims were illegal abortion with severe complications such as peritonitis, rupture of uterine, small intestine, rectum, and mesentery perforation. Three cases had consumed misoprostol (prostaglandin E2) and one case had used prostaglandin E1 before curettage. Misoprostol was also used significantly more frequently than other methods for abortion before curettage (P < 0.05). Minor and short-term complications did not registered. Conclusion: The feature of claims showed that only severe morbidity and complications were registered in medical court. The definition of illegal abortion as a criminal act can be one of the factors of decreasing of abortion's complication claims.